The Potency of Propolis on Honey Bees Nest on Inhibiting The Infection of P. Falciparus as Supporting Therapy on Malaria Tropicana - Azizah, Nurul; Kencono Wungu, Citrawati Dyah; Viradella, Jofan (The Journal of The Indonesian Medical Students Association, 2010)
The incidence of malaria in Indonesia increases every year, even reached seven times higher in 2000 thank that in 1997. This disease is caused bt Plasmodium parasite. Plasmodium falciparum and Plasmodium vivax are the most common species, but the deadliest one is Plasmodium falciparum. However, there are many P. falciparum cases resistant to antimalaria drugs. Hence, it is necessary to look for other antimalaria drugs as alternative therapy.There are many medicating effects of bees products. In this paper, we try to study propolis, a compound extracted from resin, mixed with bee wax, honey, and enzyme. Luteplin 7-O glucoside is a flavonoid compound in propolis, identified as antimalaria agent. Luteolin 7-O glucoside has specific target FabI, regulator and repressor exzyme for type 2 FAS. This compound inactivated FabI enzyme, blocked the biosynthesis of Plasmodium fatty acid, and hence disturbed the metabolism and growth of Plasmodium.Another flavonoid component of propolis, chalcone, has also important effect on blocking erythrocyte hemolysis in P. falciparum infection so symptoms can be reduced.ÃÂ Key words: P. falciparum, flavonoid, Luteolin 7-O glucoside, type21 FAS, chalcone